Effect of nitrogen content on dynamic strain ageing behaviour of type 316LN austenitic stainless steel during tensile deformation. (May 2014) - Ganesan, V.; Laha, K.; Nandagopal, M.; Parameswaran, P.; Mathew, M. D.
<x content-type="archive" xml:space="preserve">Abstract</x> The effect of nitrogen content on the dynamic strain ageing (DSA) behaviour of type 316LN austenitic stainless steel has been studied. The nitrogen content was varied from 0·07 to 0·22 wt-%. The tensile tests were carried out over a temperature range of 300–1123 K and at three strain rates in the range 3×10−3–3×10−5 s−1. Serration was observed in the load elongation curves in the intermediate test temperature range and has been considered due to DSA phenomenon. The critical strain to onset of serrated flow increased with increase in nitrogen content and strain rate. The temperature for onset of DSA and the temperature of disappearance of DSA were found to increase with the increase in nitrogen content. The variations in tensile strength and work hardening rate of the steel with temperature exhibit peak values in the intermediate temperature range and have been attributed due to DSA phenomenon. The activation energy for DSA, estimated based on the temperature and strain rate dependences of the strain to onset of serrated flow, was found to increase from 111 to 218 kJ mol−1 with the increase in nitrogen content from 0·07 to 0·22 wt-% and the increase has been attributed to the possible enhanced interaction of the DSA causing interstitial nitrogen with substitutional chromium.